Recent Advances and Applications in Paper-Based Devices for Point-of-Care Testing - Hou, Yue; Lv, Cong-Cong; Guo, Yan-Li; Ma, Xiao-Hu; Liu, Wei; Jin, Yan; Li, Bao-Xin; Yang, Min; Yao, Shi-Yin (Journal of analysis and testing, 2022)
Point-of-care testing (POCT), as a portable and user-friendly technology, can obtain accurate test results immediately at the sampling point. Nowadays, microfluidic paper-based analysis devices (μPads) have attracted the eye of the public and accelerated the development of POCT. A variety of detection methods are combined with μPads to realize precise, rapid and sensitive POCT. This article mainly introduced the development of electrochemistry and optical detection methods on μPads for POCT and their applications on disease analysis, environmental monitoring and food control in the past 5 years. Finally, the challenges and future development prospects of μPads for POCT were discussed.